The Chinese face of Jesus Christ, Volume 4b, Supplementary anthology general index addenda - Malek, Roman 1951-2019 (Monumenta Serica Monograph Series, 2019)
This volume completes the previous volumes 1, 2, 3a, 3b, and 4a of an interdisciplinary book project on the reception of Jesus Christ in China, as seen from the perspectives of Sinology, mission history, theology, and art history, among others. It consists of the following parts: A "Supplementary Anthology" that presents excerpts and longer quotations from selected works - such as translations, prayers, poems, and scholarly articles - listed in the bibliography of vol. 4a; two sections of "Notes on Contributors, Vols. 1-3b" and "Notes on Authors of the Anthologies, Vols. 1-3b, 4b" that provide short biographical information on the contributors of articles and authors of all texts in the anthologies; a "List of Reviews of Vols. 1-4a" published on the whole collection as well as on individual volumes; the Tables of Contents of vols. 1, 2, 3a, 3b and 4a; a "General Index and Glossary" that gives readers access to all articles and anthologies included in vols. 1, 2, 3a, 3b, and 4b, a corpus of almost two thousand pages of text; and finally a list of "Errata and Corrigenda."